To Study the Prevalence of Areca Nut Induced Oral Submucous Fibrosis in Patients Visiting Dental OPD of Shalinitai Meghe Hospital and Research Center Nagpur: A Demographic Study - Saroj Kuthe1, Swati Maldhure2 , Gargi Nimbulkar3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Oral submucosal fibrosis (OSMF) is now recognized internationally as an Indian disorder.This has one of the highest percentages of malignant transition between oral lesion and condition potentiallymalignant, Consequently, it is a source of concern for oral medical practitioners. The goal of the presentstudy is to assess the frequency of OSMF among betel nut chewers in various group of age.Research Methodology: Collectively 80 OSMF sufferers in dentist OPD of Shalinitai Meghe Hospitaland research center, Nagpur over a period of 4 months (1 December 2019 to 21 March 2020) Chosenfor the analysis. A comprehensive history of the case and a clinical test was carried out under displayedillumination. OSMF diagnosis was based on mouth opening troubles and blanched oral mucosa, markedwith noticeable fibrous bands. Many diagnostic features included sensation of pain, salivation, protrusion ofthe tongue, behaviors and related malignant changes. The study was conducted based on age group, periodof the habit, habit frequency and habit form. Simple correlation analysis was performed.Results: of OSF’s 80 cases searched, 37 (46.25%) cases were in stage II, 27 (33.75%) were stage III, 9(11.25 %) stage I, and 7 (8.75 %) stage IV. Based upon age group, group III (30--40 years) Had been moreprominent than the others. Areca nut (gutkha) was an important etiologic agent (55.8%) as compared withother etiological agent.Conclusion: The high incidence of OSMF in the general population requires a substantial understandingand treatment of these lesions. Primary health care practitioners and dentists should be informed and familiarwith these lesions, including etiology and pathogenesis, clinical appearance, treatment and management.